PENGARUH IMPULSIVE BUYING DAN REGULASI DIRI TERHADAP PERILAKU BERUTANG PADA MAHASISWA PENGUNA SHOPEEPAYLETER DI UIN ANTASARI - Abbas, Ma'arif; Faridah, Siti (Faculty of Ushuluddin and Humanities, 2024)
This study aimed to examine the influence of impulsive buying and self-regulation on debt behavior among university students who use ShopeePayLater. The research employed a quantitative approach with a survey method. The sample consisted of 322 ShopeePayLater users from UIN Antasari Banjarmasin, selected through purposive sampling. Data were collected using scales for impulsive buying, self-regulation, and debt behavior, and analyzed using multiple linear regression. The results indicated that impulsive buying and self-regulation simultaneously have a significant effect on debt behavior with a significance value of 0.000 (p < 0.05). The coefficient of determination (R^2) was 0.264, indicating that these two variables jointly explain 26.4% of the variance in debt behavior among ShopeePayLater users.